Pengaruh Financial Knowledge, Love of Money dan Financial Attitude terhadap Financial Management Behavior pada Generasi Z di Kota Jambi - Rizki, Sri Ajeng Sukmala; Setiawati, Rike; Utama, Ahmad Nur Budi (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of financial knowledge, love of money, and financial attitude on financial management behavior in Generation Z in Jambi City. This study uses a quantitative approach with a survey method involving 100 respondents from Generation Z in Jambi City. Data were collected through a questionnaire specifically designed to measure the variables studied. The data used are primary data obtained through a questionnaire with a Likert scale. The data analysis method in this study uses PLS (partial least square) using Smart PLS 3.0. The results of this study indicate that financial knowledge and financial attitude have a positive and significant effect on financial management behavior while love of money has a negative and insignificant effect on financial management behavior in Generation Z in Jambi City.